Secondary Sphincter Repair for Anal Incontinence Following Obstetric Sphincter Injury: Functional Outcome (Journal of Surgical Sciences, 2022)
Background: Secondary Repair of Anal Sphincter may be necessary if Primary repair of obstetric anal sphincter injuries (OASIS) is complicated by wound rupture or infection. When OASIS is treated for anal incontinence, it is considered a secondary repair even if no primary repair has been performed during the postpartum period. Home delivery and failure to reach into the health care delivery system is important cause of OASIS. The objective of this study was to assess the functional outcomes, morbidity, and impact of quality of life (QoL) following secondary repair of OASIS.Methods: Our subject were 26 patients whose old complete perineal tear were repaired in 3 hospitals, in Dhaka city, Bangladesh over a 5-year period. The layering technique of repair was used. Function improved in 24 of 26 patients (92%) with adequate follow-up. The function was completely restored in 22 of 26 patients (85%). Data on age, incontinence to flatus, solid or liquid stools, duration of symptoms, history of the previous repair, duration of the repair, post-operative stay, complications, and recovery were collected and analyzed.Results: A total of 26 patients underwent secondary anal sphincter repair for incontinence. The average duration of surgery was 90 minutes. The majority of patients were in the younger age groups, with a mean age of 34.0±12.1 years. The Wexner score significantly improved after surgery, decreasing from 15.12±4.34 preoperatively to 5.68±1.13 postoperatively (p